2022
DOI: 10.4102/td.v18i1.1209
|View full text |Cite
|
Sign up to set email alerts
|

The use of English to offer learner support and enhance perceptual skills development in South African township schools

Abstract: Research has identified the underdevelopment of perceptual skills as a cause of lifelong learning struggles and the restriction of developmental progress in learners. The literature also indicates that early intervention is one strategy that effectively mitigates the long-term effects thereof through learner support. However, the inadequacy of in-service teachers’ skills to assess perceptual skills development, coupled with the implementation of the teaching and learning language policy, are issues for concern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Schools present and represent unique environment that may not be easily reproduced or choreographed. Studies on the conduct of teaching practice (Aigbavboa et al, 2018;Robinson & Rusznyak, 2020;Thuketana, 2020) have shown immense support for school-based sessions in which the school setting provides a natural environment for real experience. It is for this reason that some researchers such as Robinson and Rusznyak (2020) suggest that ideally student teachers should be exposed to various school contexts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Schools present and represent unique environment that may not be easily reproduced or choreographed. Studies on the conduct of teaching practice (Aigbavboa et al, 2018;Robinson & Rusznyak, 2020;Thuketana, 2020) have shown immense support for school-based sessions in which the school setting provides a natural environment for real experience. It is for this reason that some researchers such as Robinson and Rusznyak (2020) suggest that ideally student teachers should be exposed to various school contexts.…”
Section: Discussionmentioning
confidence: 99%
“…Teaching practice represents the nexus between theory and practice (Aigbavboa et al, 2018;Thuketana, 2020). The practicum gives teacher interns the chance to apply the knowledge and theories learnt from study programs to classroom situations (Adu-Yeboah & Kwaah, 2018;Schaffer & Welsh, 2014).…”
Section: The Role Of School-based Teaching Practice In Teacher Prepar...mentioning
confidence: 99%
“…Management of linguistic diversity in post-apartheid South Africa has been made problematic by the dearth of an irrefutably definite language policy, leading to the use of English and Afrikaans as the most authoritative languages in the socio-economic and political territories of its society. The policy framework not only initiates an unwithered approach to multilingualism in South Africa, but strongly encourages the use of indigenous languages as official languages in order to foster and promote national unity (Thuketana & Makgabo 2022). The policy framework takes into account the broad acceptance of linguistic diversity, social justice, the principle of equal access to public services and programs, and respect for language rights (Makoni et al 2023).…”
Section: Research Methodology and Conceptual Frameworkmentioning
confidence: 99%
“…In the current study, we attempt to understand how the voices of HE community partners could influence HE-CE practice (Andrews 2011). We note that little research has been conducted into CE in South Africa (Bender 2008); however lately there is a growing interest and publications in the field of CE (Bobo and Akhurst 2019;Machimana et al 2020;Thuketana 2020).…”
Section: Social and Cognitive Justice In The Higher Education Agendamentioning
confidence: 99%